Adding IPv6 support to H323 Gnomemeeting/openH323 port - Christos Bouras; Apostolos Gkamas; Kostas Stamos; S Josset (11th International Conference on Software, Telecommunications and Computer Networks (SoftCOM 2003), Croatia, Italy, 2003)
This article deals with the port towards the new IPv6 Internet network of voice and multi-media over IP applications. We explain in detail our experience in porting Gnomemeeting, the well-known Linux based videoconference software, and more particularly the H323 library which implements the signaling protocols (call establishment, transfer, codec negotiation,…).